Mechanisms and Recent Advances of Small-Molecule Therapeutics in Rosacea Treatment - Ye M; Hao P; Luo N; Li T (Clinical, Cosmetic and Investigational Dermatology, 2025)
Maogen Ye,1,2 Pingsheng Hao,1 Nana Luo,1 Tianhao Li1 1Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, 610000, People’s Republic of China; 2Chengdu University of Traditional Chinese Medicine, Chengdu, 610000, People’s Republic of ChinaCorrespondence: Pingsheng Hao, Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, 610000, People’s Republic of China, Tel/Fax +86-28-87769902, Email hpswl@126.comAbstract: Rosacea is a common dermatological disease, and the complexity of its etiology and pathogenesis makes conventional treatment of rosacea difficult. Small-molecule drugs are a new option for the treatment of rosacea. Based on its good efficacy, convenience of use, affordable price and other advantages, more and more small-molecule drugs are used in the treatment and management of rosacea, involving a variety of molecular pathways, including JAK/STAT signaling pathway, TRPV, TLR2-KLK5-LL37 and mTOR pathways, Th1/Th17-IL17, PED-4, AhR and MRGPRX2. However, the specific treatment mechanism and research progress have not been systematically elucidated. This review summarizes the latest advances in small molecules targeting key inflammatory pathways in rosacea, provides new ideas for the treatment of rosacea and new directions for the clinical management of rosacea. In addition, we need to pay attention to individual differences in patients, the side effects of drugs and formulations. Therefore, further research on small-molecule drugs for the treatment of rosacea is very necessary.Keywords: rosacea, small-molecule drugs, mechanism of action